KH. MUHAMMAD NAWAWI: Tokoh Nahdaltul Ulama dan Laskar Hisbulloh Mojokerto 1929-1946 - Izzul Mudoffar, A; Afiyanto, Hendra (Tanjak: Sejarah dan Peradaban Islam, 2023)
Muhammad Nawawi is a village kiai who is one of the founders of Nahdlatul Ulama Mojokerto and the first Islamic madrasa in Mojokerto. During the war in 1945 in Surabaya, KH Muhammad Nawawi was also active in the battle as a member of the Laskar Hisbullah Mojokerto. In this study, there are three formulations of the problem, first, how is the biography and life journey of KH. Muhammad Nawawi? Second, what is the role of KH. Muhammad Nawawi in Mojokerto's Nahdlatul Ulama? Third, how did KH Muhammad Nawawi contribute to Laskar Hisbullah in Mojokerto? This study aims to determine the form of KH Muhammad Nawawi's dedication to the people of Mojokerto. This study uses historical research methods, namely: heuristic, source verification, interpretation, and historiography. Some of the findings include: first, KH Muhammad Nawawi is the son of Munadi who has a lineage from KH Mutamakkin, second, KH Muhammad Nawawi is the founder of Nahdlatul Ulama Mojokerto, who actively descends to the branch, third, KH Muhammad Nawawi is a member of the Hizbullah ranks who participated in fighting the allies in the Surabaya war.